Managing Hypertension: The Role of a Food Scientist and Nutritionist - Egwumah, Ojochenemi; Girgih, Abraham; Joshua, Victoria (AlQalam Journal of Medical and Applied Sciences, 2022)
Hypertension can result in myocardial infarction, renal failure, strokes, and death. It is a hemodynamic condition that is accompanied by an increase in peripheral vascular resistance. One billion individuals are believed to be affected by hypertension. This work seeks to provide an exhaustive synthesis of the theoretical and experimental data presented in various publications in order to determine the role of a food scientist and nutritionist in managing hypertension using functional food. Apart from that, the use of nutraceuticals in the management of hypertension, dietary habits in relation to trends in the management of high blood pressure coupled with the use of traditional medicines and medical foods in the management of hypertension, were discussed. Functional foods have bioactive ingredients that have been associated to restricting cholesterol absorption, which is a key element in lowering blood pressure. Functional foods, nutraceuticals, the DASH diet, conventional drugs, and medicinal foods have been found to minimize the need for antihypertensive medications, improve cardiovascular health, lower rates of morbidity and mortality, and lower healthcare expenditures. In order to treat hypertension, it is advocated that people use functional foods, nutraceuticals, folk medicine, and medical foods because they are more widely available, and safe than pharmaceutical drugs.